Photosynthetic characterization of transgenic Synechocystis expressing a plant thiol/disulfide-modulating protein. (1st February 2020) - Wessendorf, Ryan L.; Lu, Yan
ABSTRACT: A previous study showed that introducing an Arabidopsis thaliana thiol/disulfide-modulating protein, Low Quantum Yield of Photosystem II 1 (LQY1), into the cyanobacterium Synechocystis sp. PCC6803 increased the efficiency of Photosystem II (PSII) photochemistry. In the present study, the authors provided additional evidence for the role of AtLQY1 in improving PSII photochemical efficiency and cell growth. Light response curve analysis showed that AtLQY1-expressing Synechocystis grown at a moderate growth light intensity (50 µmol photons m −2 s −1 ) had higher minimal, maximal, and variable fluorescence than the empty-vector control, under a wide range of actinic light intensities. Light induction and dark recovery curves demonstrated that AtLQY1-expressing Synechocystis grown at the moderate growth light intensity had higher effective PSII quantum yield, higher photochemical quenching, lower regulated heat dissipation (non-photochemical quenching), low amounts of reduced plastoquinone, and higher amounts of oxidized plastoquinone than the empty-vector control. Furthermore, growth curve analysis indicated that AtLQY1-expressing Synechocystis grew faster than the empty-vector control at the moderate growth light intensity. These results suggest that transgenic expression of AtLQY1 in Synechocystis significantly improves PSII photochemical efficiency and overall cell growth.